Holographic Dark Energy Model With Time Varying Deceleration Parameter - P. Wankhade, R (International Journal of Advanced Astronomy, 2018)
Two minimally interacting fluids; dark matter and holographic dark energy components has been studied in a spatially homogeneous and anisotropic Bianchi type-I space-time. The solutions of the Einsteinâ€™s field equations are obtained under the assumption of time varying deceleration parameter (Abdussattar and S. Prajapati, Astrophys. Space Sci. 331, 65, 2011) which represents transition of the universe from the early decelerating phase to the recent accelerating phase. It is shown that for large expansion the model reduces to model while for suitable choice of interaction between dark matter and holographic dark energy the anisotropy parameter of the universe approaches to zero for large cosmic time and the coincidence parameter increases with increase in time. Allowing for time dependent deceleration parameter the solutions of the field equations and some physical and geometric properties of the model along with physical acceptability of the solutions have also been discussed in details.Â
Keywords: Bianchi Type-I Space-Time; Time Varying Deceleration Parameter; Holographic Dark Energy.